Human soft tissue sarcomas harbor an intratumoral viral microbiome which is linked with natural killer cell infiltrate and prognosis - William J Murphy; Robert J Canter; Nikhil Joshi; Sean J Judge; Morgan A Darrow; Steve W Thorpe; Alicia A Gingrich; Lauren M Perry; Sylvia M Cruz; Kara T Kleber; Louis B Jones; Ugur N Basmaci; et al. (Journal for ImmunoTherapy of Cancer)
Background Groundbreaking studies have linked the gut microbiome with immune homeostasis and antitumor immune responses. Mounting evidence has also demonstrated an intratumoral microbiome, including in soft tissue sarcomas (STS), although detailed characterization of the STS intratumoral microbiome is limited. We sought to characterize the intratumoral microbiome in patients with STS undergoing preoperative radiotherapy and surgery, hypothesizing the presence of a distinct intratumoral microbiome with potentially clinically significant microbial signatures.Methods We prospectively obtained tumor and stool samples from adult patients with non-metastatic STS using a strict sterile collection protocol to minimize contamination. Metagenomic classification was used to estimate abundance using genus and species taxonomic levels across all classified organisms, and data were analyzed with respect to clinicopathologic factors.Results Fifteen patients were enrolled. Most tumors were located at an extremity (67%) and were histologic grade 3 (87%). 40% were well-differentiated/dedifferentiated liposarcoma histology. With a median follow-up of 24 months, 4 (27%) patients developed metastases, and 3 (20%) died. Despite overwhelming human DNA (>99%) intratumorally, we detected a small but consistent proportion of bacterial DNA (0.02–0.03%) in all tumors, including Proteobacteria, Bacteroidetes, and Firmicutes, as well as viral species. In the tumor microenvironment, we observed a strong positive correlation between viral relative abundance and natural killer (NK) infiltration, and higher NK infiltration was associated with superior metastasis-free and overall survival by immunohistochemical, flow cytometry, and multiplex immunofluorescence analyses.Conclusions We prospectively demonstrate the presence of a distinct and measurable intratumoral microbiome in patients with STS at multiple time points. Our data suggest that the STS tumor microbiome has prognostic significance with viral relative abundance associated with NK infiltration and oncologic outcome. Additional studies are warranted to further assess the clinical impact of these findings.